Decoding geochemical signals of the Schwalbenberg Loess-Palaeosol-Sequences –Bulk Geochemical and Granulometric data - Mathias Vinnepand; Peter Fischer; Olaf Jöris; Ulrich Hambach; Christian Zeeden; Philipp Schulte; Kathryn E Fitzsimmons; Charlotte Prud extquotesinglehomme; Zoran Perić; Wolfgang Schirmer; Frank Lehmkuhl; Sabine Fiedler; et al. (PANGAEA, 2022)
In this study, we present a granulometric- and geochemical dataset for the Schwalbenberg Loess-Palaeosol-Sequence (LPS) in the Middle Rhine Valley (Germany) that covers the Upper Pleistocene in a resolution so far unprecedented for continental records in western Central Europe. Complexities in formation of loess deposits cause interfering geochemical signatures (e.g., provenance- vs. weathering- signals) limiting a straight-forward interpretation. In this context we used multivariate statistics that integrate information on grainsize (Laser Diffraction Particle Sizer) and geochemistry (XRF, ICP-OES) indicative for provenance shifts, mineral sorting during transport and reworking and weathering into Principal Component Analyses and Linear Discriminant Analyses. Our approach provides a key for tracing ecological changes throughout climate oscillations across continents.